Hybrid Contract Perbankan Syariah perspektif Maqasid al Sharia Jasser Auda - Achmad Fageh; Maulana Surya Ihsan (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2022)
This study aims to determine the relevance of the Multi-Contract concept to the theory of Maqasid Jasser Auda, as well as explain how the laws that apply the Maqasid concept to the financial system with the latest patterns in the Islamic economic world. The method used in this research is qualitative with a library research approach. Based on the results of research on the Multi Contract concept in Jasser Auda's maqasid perspective, carrying out the DSN-MUI fatwa on hybrid contracts as an effort to contextualize between Multi Akad which is in line with Islamic banking, and the sharia Maqashid concept offered by Jasser Auda which is considered more comprehensive, contextualist, elastic and moderate